Cultural Relativism as a Theory of Values - Gendrolis, Edmundas (Problemos, 1979)
A critical review of the theory of cultural relativism by M. J. Herskovits, who made an attempt to formulate an objective criterion to estimate phenomena of foreign cultures, is presented. The cultural relativism as a theory of values, however, has not brought forward any positive alternative to ethnocentrism and it suffered from methodological inconsistency. However it was of special importance in fighting against ethnocentrism, thus stimulating research in- values at intercultural aspect.